The use of surface electromyography to assess transfemoral amputees: methodological and functional perspective - Rafaella C. Silva; Thanyze A. V. Zoccoli; Vera R.F.S. Marães (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: Surface electromyography (sEMG) has been established as a safe non-invasive method to investigate neuromuscular function. However, the use of this instrument to assess lower limbs of transfemoral amputees still presents a lack of standardization in its methods of signal acquisition and processing. The aim of this study was to review the current state of sEMG utilization to assess transfemoral amputees, the procedures adopted for the acquisition and the functional findings. Methods: This is a literature review. Five electronic databases were searched to find the studies: All relevant information of each study was extracted and registered. Methodological quality was evaluated using a customized checklist. Results: Eight studies followed the inclusion criteria and were included in this paper. Four studies did not reach more than 80% of the quality checklist, few studies fully described the methodology applied. The muscles assessed were similar in all studies, electrodes placement was determined by different criteria. Conclusion: This paper demonstrates that a few studies have used this method to assess this population and the main variable aspect is concerned to the placement of the electrodes. More researches are needed to better understand the neuromuscular behavior of amputees by using sEMG and assist future researches to develop more reproducible and reliable studies.